CLUSTERING LQ45 INDEXED COMPANIES BASED ON FINANCIAL PERFORMANCE INDICATORS USING THE TWO-STEP CLUSTER METHOD - Putri, Nurweni; Wulandari, Wahyuni (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The company's financial performance is one of the bases for assessing the company's financial condition which is carried out based on analysis of the company's financial ratios. Financial performance has an influence on the number of investors in a company. Indicators for measuring the company's financial performance include return on assets, return on equity, net profit margin, gross profit margin, operating profit margin, yield, payout, asset growth and company stability. Based on the company's financial performance indicators, company clustering will be carried out. One of the mathematical analysis approaches used to cluster companies based on financial performance indexed by LQ45 is to use the two-step cluster method. This method is the method used because the data variables to be processed are numerical data variables and categorical variables. The company's optimal cluster solution obtained is in the form of 3 optimal clusters. In cluster 1 a cluster of companies was formed which had the largest payout and yield values, in cluster 2 a cluster of companies was formed which had the largest net profit margin, gross profit margin, operating profit margin and cluster 3 was formed a cluster which had return on assets values, largest return on equity. Thus, it can be seen that each cluster has different characteristics.